Hemostatic absorbable gelatin sponge loaded with 5-fluorouracil for treatment of tumors - Sun W (Dove Medical Press, 2013)
Wei Sun,1 Yinghui Chen,2 Weien Yuan3 1School of Pharmaceutical Sciences, Jilin University, Changchun, People’s Republic of China; 2Department of Neurology, Jinshan Hospital, Fudan University, Jinshan District, Shanghai, People’s Republic of China; 3School of Pharmacy, Shanghai Jiao Tong University, Shanghai, People’s Republic of China Background: Surgical tumor resection is the main treatment for tumors however the treatment process often results in massive bleeding and tumor cell residue. The main aim of this research was to address problems such as bleeding, systemic chemotherapy side effects while enhancing quality of life, and increasing drug concentrations at the tumor site by developing a novel formulation with local long-term efficacy for treatment of tumors and to stop bleeding. Methods: 5-Fluorouracil (5-FU) was suspended in an ethyl acetate solution of poly D,L-lactide-co-glycolic acid (PLGA) and a vacuum drying method was applied. The hemostatic gelatin sponge loaded with 5-FU was prepared by absorption of the suspension. The in vitro and in vivo characteristics of the hemostatic gelatin sponge loaded with 5-FU (5-FU-HAGS) were investigated. Results: 5-FU-HAGS (hemostatic absorbable gelatin sponge loaded with 5-fluorouracil) was successfully produced with controlled release of the content and was reproducibly suitable for local tumor treatment as an implant to stop bleeding. The encapsulation efficiency of 5-FU-HAGS was above 98%. The in vitro 5-FU release kinetic profile matched a near zero-order equation for 20 days. The in vivo 5-FU plasma concentration was at a more stable level than when 5-FU solution was administered by subcutaneous injection. Bleeding can be stopped more effectively by coating a piece of blank gelatin sponge. The survival ratio of tumor-bearing mice using a 5-FU-HAGS subcutaneous implant was higher when compared to mice given a subcutaneous injection of 5-FU solution. Conclusion: The 5-FU-HAGS system is a potential and effective way of enhancing the survival ratio and improving the quality of life of tumor-bearing mice. Keywords: absorbable gelatin sponge, 5-fluorouracil, sustained-release, tumor